2013
DOI: 10.1016/j.jcmg.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

OCT-Based Diagnosis and Management of STEMI Associated With Intact Fibrous Cap

Abstract: In autopsy studies, at least 25% of thrombotic coronary occlusions are caused by plaque erosion in which thrombus often overlies atherosclerotic plaque without evident disruption of the fibrous cap. We performed optical coherence tomography imaging after aspiration thrombectomy and identified plaque erosion as the cause in 31 patients presenting with ST-segment elevation myocardial infarction. Plaque erosion was identified when the fibrous cap of the culprit lesion was intact. Based on clinical criteria, 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(87 citation statements)
references
References 2 publications
2
82
1
2
Order By: Relevance
“…Pathology studies by Virmani have shown that ACS are most often due to plaque rupture or erosion 24 ; was and these observations have been subsequently confirmed on IVUS and on OCT 24,26,27 . Fibrous cap thickness is critical to onset of these complications, thickness <65 μm being associated with high risk of rupture 28 .…”
Section: Discussionmentioning
confidence: 91%
“…Pathology studies by Virmani have shown that ACS are most often due to plaque rupture or erosion 24 ; was and these observations have been subsequently confirmed on IVUS and on OCT 24,26,27 . Fibrous cap thickness is critical to onset of these complications, thickness <65 μm being associated with high risk of rupture 28 .…”
Section: Discussionmentioning
confidence: 91%
“…This conservative strategy would avoid both early (vessel dissection, distal embolism, and acute stent thrombosis) and late (restenosis, neoatherosclerosis, and late and very late stent thrombosis) complications of stent implantation 10, 11, 12, 13, 14. Indeed, few reports with a small number of cases have suggested that a subset of patients with ST‐segment elevation myocardial infarction caused by PE might be treated by antithrombotic therapy with favorable outcome 2, 15, 16. However, data on the outcomes of patients with ACS caused by rupture or erosion are limited.…”
Section: Introductionmentioning
confidence: 99%
“…84,85) Recent studies suggest that conservative management without stenting may be an option in patients with ACS caused by plaque erosion. 86,87) OCT is the only intracoronary imaging device that can visualize plaque erosion owing to its high resolution. The EROSION study has shown the feasibility and safety of anti-thrombotic therapy without stenting in patients with ACS caused by plaque erosion.…”
Section: Tailored Management In Patients With Plaque Erosionmentioning
confidence: 99%